2005
DOI: 10.1038/sj.onc.1208685
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TGF-β type II receptor in fibroblasts promotes mammary carcinoma growth and invasion through upregulation of TGF-α-, MSP- and HGF-mediated signaling networks

Abstract: Stromal fibroblasts regulate epithelial cell behavior through direct and indirect cell-cell interactions. To clarify the role of TGF-beta signaling in stromal fibroblasts during mammary development and tumorigenesis, we conditionally knocked out the TGF-beta type II receptor gene in mouse mammary fibroblasts (Tgfbr2(fspKO)). Tgfbr2(fspKO) mice exhibit defective mammary ductal development, characterized in part by increased ductal epithelial cell turnover associated with an increase in stromal fibroblast abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
244
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(256 citation statements)
references
References 65 publications
11
244
1
Order By: Relevance
“…Finally, it is likely that LMO4 effects are context-dependent; LMO4-mediated signaling to stroma and/or other neighboring cells may be important for the pro-proliferative and pro-tumorigenic effects of LMO4 upregulation in vivo. In this regard, the identification of BMP7 as a target gene of LMO4 is relevant because BMP7 has striking effects on stromal cells (Dean et al, 2004), and it is known that growth signaling from stromal fibroblasts during mammary gland development is regulated by TGFb ligands (Cheng et al, 2005). Like LMO4, BMP7 is highly expressed in the ductular end buds of the developing mammary gland (Sum et al, 2005a, b), the site of active proliferation and stromal invasion of the mammary epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it is likely that LMO4 effects are context-dependent; LMO4-mediated signaling to stroma and/or other neighboring cells may be important for the pro-proliferative and pro-tumorigenic effects of LMO4 upregulation in vivo. In this regard, the identification of BMP7 as a target gene of LMO4 is relevant because BMP7 has striking effects on stromal cells (Dean et al, 2004), and it is known that growth signaling from stromal fibroblasts during mammary gland development is regulated by TGFb ligands (Cheng et al, 2005). Like LMO4, BMP7 is highly expressed in the ductular end buds of the developing mammary gland (Sum et al, 2005a, b), the site of active proliferation and stromal invasion of the mammary epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key signaling molecules produced by cancer-associated fibroblasts is transforming growth factor-b (TGF-b): TGF-b activates fibroblasts to increase ECM formation (Keski-Oja et al, 1988) and promotes epithelial cell and fibroblast proliferation, depending upon the complement of growth factors present in the local microenvironment (Roberts et al, 1985). Collectively, these studies support a model of tumorigenesis in which TGF-b signaling creates a permissive stromal state for epithelial cancer initiation and progression (Bhowmick et al, 2004;Cheng et al, 2005).…”
Section: Incorporating the Tumor Microenvironmentmentioning
confidence: 95%
“…Ablation of TGF-β responsiveness in fibroblasts exacerbates neoplastic progression in several tissues, including prostate, stomach, and breast, [18,28,29]. Others have reported that stromal ablation of the tumour suppressor Pten during mammary carcinogenesis results in accelerated tumourigenesis, via Ets2 inactivation, suggesting multiple pathways by which fibroblasts can inhibit neoplastic growth [30,31].…”
Section: From Tumour Suppressors To Tumour Promotersmentioning
confidence: 99%